2017
DOI: 10.1080/00223131.2017.1297742
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark study of the recent version of the PHITS code

Abstract: We performed a benchmark study for 58 cases (22 cases reported in this paper and 36 cases reported in online as supplementary materials of this paper) using the recent version (version 2.88) of the Particle and Heavy-Ion Transport code System (PHITS) in the following fields: (1) particle production cross-sections for nuclear reactions from 20 MeV to 1 GeV, (2) thick-target neutron yields and neutron shielding, (3) depth-dose distribution in water using 12 C beam, and (4) electron and photon transportation over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(63 citation statements)
references
References 51 publications
1
62
0
Order By: Relevance
“…Firstly, the compositions and mass density of materials excluding the Freiburg Flap Applicator were accurately defined in the PHITS simulation. Iwamoto et al (2017) reported that the benchmark test result to verify the accuracy of photon and electron transport using the EGS5 mode agreed with the experimental data well except for neutrons produced by photonuclear reactions with energy range from keV to GeV. In addition, the transit dose component was canceled by the adjustment of dwell time in the microSelectron HDR-v3 remote afterloading device, so that the effect was negligible.…”
Section: Summary Of Factors Of Difference Between Measured and Calculmentioning
confidence: 56%
“…Firstly, the compositions and mass density of materials excluding the Freiburg Flap Applicator were accurately defined in the PHITS simulation. Iwamoto et al (2017) reported that the benchmark test result to verify the accuracy of photon and electron transport using the EGS5 mode agreed with the experimental data well except for neutrons produced by photonuclear reactions with energy range from keV to GeV. In addition, the transit dose component was canceled by the adjustment of dwell time in the microSelectron HDR-v3 remote afterloading device, so that the effect was negligible.…”
Section: Summary Of Factors Of Difference Between Measured and Calculmentioning
confidence: 56%
“…Owing to the continuous improvement and promotion of the code, the number of registered users exceeded 2,500 in 2016, and has been rapidly increasing since then. A comprehensive benchmark calculation results of the new version of PHITS will be published elsewhere [35]. M. Adachi, Mr. T. Miura, and Mr. A. Wada of RIST for their assistance in the programing of PHITS.…”
Section: Discussionmentioning
confidence: 99%
“…A Monte Carlo simulation code, Particle and Heavy Ion Transport System (PHITS; Iwamoto et al, 2017), was used in the simulation for validating the present shielding design. The proton-beam power of the neutron source was assumed to be 1 MW.…”
Section: Radiation Shielding Design and Validationmentioning
confidence: 99%